2017
DOI: 10.1103/physreve.95.012805
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stability of particle-stabilized droplets under micropipette aspiration

Abstract: We investigate the mechanical behavior of particle-stabilized droplets using micropipette aspiration. We observe that droplets stabilized with amphiphilic dumbbell-shaped particles exhibit a two-stage response to increasing suction pressure. Droplets first drip, then wrinkle and buckle like an elastic shell. While particles have a dramatic impact on the mechanism of failure, the mechanical strength of the droplets is only modestly increased. On the other hand, droplets coated with the molecular surfactant Sodi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Essentially the same mechanical instability has been observed for liquid droplets, neutrophils ( i.e. , certain types of white blood cells), , and fibroblasts .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Essentially the same mechanical instability has been observed for liquid droplets, neutrophils ( i.e. , certain types of white blood cells), , and fibroblasts .…”
Section: Resultssupporting
confidence: 61%
“…However, for the tubulated vesicles considered here, the mechanical tension can be ignored compared to the spontaneous tension, as shown in the SI and summarized by the relation . Therefore, the elastic counter pressure as given by eq has the asymptotic form An analogous equation applies to the micropipette aspiration of liquid droplets, for which the counter pressure arises from capillary forces, and the spontaneous tension σ of the GUV is replaced by the interfacial tension of the droplet.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have confirmed such a behavior, whatever the particle size, particle shape, i.e. dumbbell [59] and ellipsoidal [4] shapes, particle nature [4,59], or bubble/drop size. We stress that all the results from literature can be gathered on the same graph by plotting the reduced collapse pressure ∆ (2 ⁄ ) ⁄ (which is equivalent to Π ⁄ ) as a function of ⁄ (see figure 2-d).…”
Section: Shrinkage Of Armored Spherical Bubbles and Dropsmentioning
confidence: 97%
“…Indeed, if the area reservoir provided by the membrane nanotubes is sufficiently large, the micropipette aspiration of the vesicles leads to a mechanical instability and to the uptake of the vesicle by the micropipette, as in Figure 10e, in close analogy to the corresponding mechanical instability that has been observed during the micropipette aspiration of a liquid droplet. [ 92–94 ]…”
Section: Elasticity Of Biomembranesmentioning
confidence: 99%